Thermodynamics, Isotherms, and Kinetics Evaluation of the (Nickel Oxide/Cerium Dioxide/Graphene Oxide Nanocomposite) for Methylene Blue (MB) Dye Removal - Mohammed A. Al-Madani; Salah A. Gnefid; Faraj M. Al-Lafi (African Journal of Advanced Pure and Applied Sciences, 2024)
Serious environmental issues are brought on by the textile industry’s excessive growth, consumption of water and dyes, particularly when it comes to excessive water body pollution. When it comes to green chemistry, adsorption is an appealing, workable, affordable, highly effective, and sustainable method for removing contaminants from water. In this research paper, Graphene oxide/nickel oxide/cerium dioxide nanocomposite (NiO/ /GO): kinetics, isotherms, and thermodynamics of adsorption behaviour method for Methylene Blue (MB) elimination from water-based solutions was examined. Langmuir, Freundlich, and Dubinin-Radushkevich isotherms were used to assess the equilibrium data. The Langmuir model provides the best explanation for the uptake of (MB) dye, suggesting that the adsorption of (MB) dyes onto (NiO/ /GO) nano-composites is monolayer and uniform. Direct dye adsorption is found to follow pseudo-first-order and pseudo-second-order models, respectively, based on an analysis of the adsorption kinetics. In the response surface methodology-determined optimal removal setting (pH 7, contact time 40 min), the maximum adsorption capacity was (105.26 mg/g). Adsorption uptake was shown to increase with increases of initial dye concentration and contact time. Furthermore, the process demonstrated endothermic nature. Changes in entropy, enthalpy, and Gibb’s free energy were (0.031, 0.073) kJ/mol.K, and -21.66 kJ/mol, respectively. The (MB) dye removal from aqueous solutions was quickly and effectively by comparing the results with those that have been published.